Parasitosis intestinal y anemia en niños de la Unidad Educativa Comunitaria Intercultural Bilingüe “Mushuk Rimak”, parroquia San Lucas, Loja - Alvarez Rebollero, Karen Lizbeth (2023)
In our country, there are several environmental, social and economic factors that affect the child population, especially in rural areas where poverty, lack of access to drinking water and poor personal hygiene are common. These factors can lead to the appearance of diseases such as anemia, which can aggravate if it’s associated with the presence of parasites, generating negative consequences in the growth, normal development and school performance of children, in addition to malnutrition. In order to identify the existence of intestinal parasites and anemia in children attending the Intercultural Bilingual Community Education Unit "Mushuk Rimak" in the district of San Lucas, Loja, a descriptive, non-experimental, cross-sectional research was carried out with the participation of 95 children from 3 to 12 years of age who fulfilled with the inclusion requirements. The coprological analysis was carried out by the method of direct detection using physiological serum and lugol to visualize and identify the types of parasites, while for the hematological analysis was used a blood sample to identify the types of anemia through the analysis of hematological biometry using the Sinothinker automated hematological counter. The results showed that 100% of the population studied presented parasitosis finding a prevalence of Entamoeba histolytica, Entamoeba coli, Ascaris lumbricoides, Blastocystis hominis, Iodamoeba bütschlii, Trichuris trichiura and finally Giardia lamblia, but it wasn’t found evidence of anemia. Therefore, we couldn't establish a relationship between intestinal parasitosis and anemia